2008
DOI: 10.1097/mog.0b013e3282f9764b
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced liver injury in 2007

Abstract: The year 2007 brought with it several reminders of the importance of drug-induced liver injury in the clinical trial as well as the clinical practice setting. There is additional evidence that statin drugs may be used safely in patients with chronic liver disease. Comments received by the US Food and Drug Administration to finalize their guidance document are eagerly awaited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 68 publications
2
42
1
6
Order By: Relevance
“…Given this common mode of injury, one could surmise a potential benefi t in pyrrolizidine-induced liver injury with pentoxyphylline. This same assumption could be applied to other botanicals thought to induce hepatocellular injury via mitochondrial toxicity and oxidative stress (eg, compounds containing usnic acid, such as kombucha tea and Atractylis gummifera [37], and Norris et al [38]. )…”
Section: Mechanisms Of Herbal Hepatotoxicity and Therapeutic Implicatmentioning
confidence: 93%
“…Given this common mode of injury, one could surmise a potential benefi t in pyrrolizidine-induced liver injury with pentoxyphylline. This same assumption could be applied to other botanicals thought to induce hepatocellular injury via mitochondrial toxicity and oxidative stress (eg, compounds containing usnic acid, such as kombucha tea and Atractylis gummifera [37], and Norris et al [38]. )…”
Section: Mechanisms Of Herbal Hepatotoxicity and Therapeutic Implicatmentioning
confidence: 93%
“…Второе место за-нимают антимикробные препараты. Кажется парадок-сальным факт, что в Азии самая частая причина гепато-токсических реакций ¬-применение фитопрепаратов [6], которые ошибочно считаются абсолютно безопас-ными, «созданными самой природой» агентами.…”
Section: безопасность статиновunclassified
“…Chronic pain conditions comprised five of the 11 top-ranking conditions for years lived with disability in 2010 (Vos 2012), and are responsible for considerable loss of quality of life and employment, and increased healthcare costs (Moore 2014a). In systematic reviews, the overall prevalence of neuropathic pain in the general population is reported to be between 7% and 10% (van Hecke 2014), and about 7% in a systematic review of studies published since 2000 (Moore 2014a (Norris 2008). One study evaluating all cases of acute liver failure leading to registration for transplantation (ALFT) across seven European countries for a three-year period showed that paracetamol overdose was responsible for one sixth of cases of ALFT, though this varied considerably between each country (Gulmez 2015).…”
Section: Description Of the Conditionmentioning
confidence: 99%